Redistribusi Tanah Objek Reforma Agraria (TORA) Guna Mewujudkan Kesejahteraan Masyarakat Dalam Rangka Percepatan Pelaksanaan Reforma Agraria - Elsani Mulyaputri (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Departing from the guidelines of the nation's noble ideals to prosper the people's lives, the government through the Agrarian Reform program aims to change the unequal agrarian structure by redistributing land to the community, especially farmers, so as to create social and economic justice. The purpose of this study is to find out and describe the redistribution of Land Object of Agrarian Reform (TORA) in the context of accelerating the implementation of agrarian reform and the implementation of agrarian reform in order to realize community welfare. This research is processed with a normative juridical approach method, namely by looking at law as a set of regulations/rules or doctrines that have a normative nature (law in book). The results of the TORA redistribution problem in the context of accelerating the implementation of agrarian reform have not been fully achieved, especially in the redistribution of forest area land. Agrarian reform has had a significant impact on improving people's welfare but it is not comprehensive, it is hoped that all elements can succeed in agrarian reform.